PERAN KEPEMIMPINAN DALAM PENINGKATAN KINERJA KARYAWAN DI PT. GARUDA KARYA MANDIRI PERSPEKTIF KOMUNIKASI - Dinantara, Mohamad Dudy; Krisyanto, Edy; Marthadinata, Suryadi (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2021)
This study aims to (1) analyze the role of leadership and leader communication in improving employee performance at PT Garuda Karya Mandiri (2) analyze the typology of leadership communication applied by the leaders of PT Garuda Karya Mandiri. The findings of this study are expected to be able to determine the role of leadership and communication practices that should be carried out by a superior to his subordinates in running a company organization. Where we know that in the era of free competition that is so tight today, optimal performance for companies is a price of necessity to stay afloat while paying attention to the values of the mood of its employees. In an effort to always maintain employee performance so that it is always optimal, it is necessary for the role of leadership communication to achieve work targets in the company. Communication made by superiors should be interactive, humanistic and constructive so that each employee can carry out and enjoy their respective jobs. The results of research on the role of leadership in improving employee performance (respectively Communication) are: (1). Leaders as examples and role models, (2). Important decision makers, (3). Leaders as communicators, (4). Leaders as evaluators. Thus in the end it can be seen that through the role of leadership and communication carried out by a leader well, he will be able to maintain the mood of the employees so that it will have an impact on the realization of optimal performance in running the company's organization.